HF-Induced Artificial Injection of Energetic Electrons from the Earth’s Radiation Belt as a Powerful Source for Modification of Ionized and Neutral Components of the Earth’s Atmosphere - Vladimir L. Frolov; Arkady V. Troitsky (Atmosphere, 2023)
It has been found in experiments at the SURA mid-latitude heating facility that the modification of the ionospheric F2 layer by powerful HF radio waves gives rise to artificial injection of energetic electrons from the Earth’s radiation belt into the atmosphere. The spectral, energy, and spatial characteristics of such an injection are presented in the paper. It is significant that the energetic electrons excite the atoms and molecules of the atmosphere to Rydberg energy levels, followed by the transition of the excited atoms and molecules to lower energy states, accompanied by the radiation of the microwave electromagnetic emissions. It has been shown that the artificial injection of energetic electrons can be considered as an independent powerful source of generation of secondary artificial turbulence, the effect of which manifests itself at ionospheric and mesospheric heights both near the heating facility and at a large distance from it up to a thousand or more kilometers. Examples of such generation are given.